Error control method using crossed axes strategy in the five-axis thread milling process - Jinjie Jia; Wenyuan Song; Mingcong Huang; Ye Zhang; Xinman Yuan; Xicheng Zhang; Dan Tang; Tingyu Zhang; Zhao Xue; Yan Jiang (Scientific Reports)
Abstract Thread milling plays a critical role in the machining of aviation components. However, for parts with complex shapes and high precision requirements, traditional three-axis milling often results in significant errors, making it difficult to meet the stringent machining specifications. In this paper, an error control method based on a crossed axes strategy for five-axis thread milling is proposed. Firstly, the thread profile is constructed using both the axial cross-section and the normal section. The geometry of the thread mill is derived from the nominal profile on the axial cross-section. Then, the tool path is defined, where a new locus is introduced to control milling errors. Building upon this, the envelope theory is employed to establish an error model for the milling process, and the errors under different milling strategies are compared. Finally, the impact of the fixed angle on machining errors is analyzed, and experiments are conducted to compare the thread milling performance of three-axis and five-axis. The results demonstrate that as the fixed angle changes from 0 to 0.0282 radians, the angle error shifts from −0.796 to 0.808 degrees, and by selecting an optimal fixed angle in 5-axis milling, the error can be minimized, validating the superior machining accuracy and effectiveness of the proposed approach.